Perkembangan Website Profiling Untuk Usaha Kuliner MAMA YUMMY - bernadhed bernadhed (Jurnal Pengabdian Mitra Masyarakat (JPMM), 2020)
MAMA YUMMY runs from the beginning of 2015 by selling culinary products in the form of silkworm foods and some pastries that are sold in general. Marketing is only done around housing or recitation events and the general public agenda. At present, MAMA YUMMY's business runs with the sales concept that has been proposed previously with the concept of the logo, packaging design and variants of the proposed product.